Projected Reality - Content Delivery Right onto Objects of Daily Life - Ehnes, Jochen; Hirose, Michitaka (International Journal of Virtual Reality, 2006)
Spatial augmented reality using controllable projector-camera-systems to project onto objects directly, or Projected Reality as we call it, offers the possibility to augment objects without requiring their users to wear or carry any devices. In order to provide the freedom of movement to users, we developed an architecture that allows projected applications to roam a network of projection units to follow the users. The concept of connecting physical objects with content in form of projected applications, although devised for projection based augmented reality systems, can be applied to HMD based or hand held AR systems as well. After a description of our AR projection system and a example application that could be used to provide location specific information to travelers using public transportation systems, we will lay out our vision of a system that may be able to provide content on a global scale